(untitled) (Modern American Journal of Medical and Health Sciences, 2026)
As the global population ages, geriatric nursing has emerged as a specialized field dedicated to managing the complex physiological, psychological, and social needs of older adults. This article explores the core tenets of geriatric care, focusing on the management of multi-morbidity, the prevention of functional decline, and the critical role of specialised nursing interventions in enhancing quality of life. By shifting from a traditional acute-care model to a holistic, person-centred approach, geriatric nurses address specific syndromes such as frailty, sarcopenia, and cognitive impairment. The discussion emphasises that high-quality geriatric care requires not only clinical expertise in age-related pathology but also an advocacy-based approach that respects the autonomy and dignity of the elderly within modern healthcare systems.